2021
DOI: 10.1073/pnas.2021915118
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier opening by intracarotid artery hyperosmolar mannitol induces sterile inflammatory and innate immune responses

Abstract: Intracarotid arterial hyperosmolar mannitol (ICAHM) blood–brain barrier disruption (BBBD) is effective and safe for delivery of therapeutics for central nervous system malignancies. ICAHM osmotically alters endothelial cells and tight junction integrity to achieve BBBD. However, occurrence of neuroinflammation following hemispheric BBBD by ICAHM remains unknown. Temporal proteomic changes in rat brains following ICAHM included increased damage-associated molecular patterns, cytokines, chemokines, trophic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 115 publications
0
25
0
Order By: Relevance
“…Importantly, FUS is not the only approach to report this occurrence. Mannitol-based BBB modulation was reported to induce a sterile inflammation response (SIR) resemblant to FUS just minutes after intracarotid arterial administration of mannitol [265]. Burks et al optimistically regard this finding as a potential application for neuroimmunomodulation, and while it could indeed have uses in various immune-based therapies for CNS diseases such as CAR-T in treating glioblastoma [266], the systemic effect of mannitol-based BBB disruption upon the CNS demands careful and diligent monitoring of this phenomenon in future clinical trials.…”
Section: Bbb Modulation and Sterile Inflammationmentioning
confidence: 99%
“…Importantly, FUS is not the only approach to report this occurrence. Mannitol-based BBB modulation was reported to induce a sterile inflammation response (SIR) resemblant to FUS just minutes after intracarotid arterial administration of mannitol [265]. Burks et al optimistically regard this finding as a potential application for neuroimmunomodulation, and while it could indeed have uses in various immune-based therapies for CNS diseases such as CAR-T in treating glioblastoma [266], the systemic effect of mannitol-based BBB disruption upon the CNS demands careful and diligent monitoring of this phenomenon in future clinical trials.…”
Section: Bbb Modulation and Sterile Inflammationmentioning
confidence: 99%
“…In the central nervous system of mammals, the BBB is created at the level of the endothelial brain cells, where multiple protein complexes accumulate at the cell-junctions, restricting the paracellular diffusion of ions and other polar solutes, hence effectively blocking the penetration of macromolecules. Unfortunately, therapeutic hyperosmolar agents can reversibly open thigh junctions in the cerebrovascular endothelium, and their conductivity depends on the degree of plasma hyperosmolality [ 87 , 88 , 89 , 90 ]. An experimental study has shown a temporal induction of neuroinflammatory response following intracarotid infusion of mannitol [ 89 ].…”
Section: Plasma Hyperosmolality and The Blood–brain Barriermentioning
confidence: 99%
“…Unfortunately, therapeutic hyperosmolar agents can reversibly open thigh junctions in the cerebrovascular endothelium, and their conductivity depends on the degree of plasma hyperosmolality [ 87 , 88 , 89 , 90 ]. An experimental study has shown a temporal induction of neuroinflammatory response following intracarotid infusion of mannitol [ 89 ]. Elevation of cytokines, chemokines, trophic factors, and cell adhesion molecules was noted within 5 min after mannitol administration that persisted for 4 days.…”
Section: Plasma Hyperosmolality and The Blood–brain Barriermentioning
confidence: 99%
“…The US FDA approves the use of arterial mannitol infusions for enhancing delivery of chemotherapeutic agents to brain tumors. Hyperosmotic solutions cause rapid shrinkage of BECs, temporarily increasing the rate of transcytosis and disrupting TJs [ 23 ]. In addition, the use of transcranial focused ultrasound is a highly promising, less-invasive method for improving drug delivery to targeted brain regions, including tumors [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%